Processes at lithium-hydride/deuteride surfaces upon low energy impact of H/D - Krstic, P.S.; Ostrowski, E.T.; Dwivedi, S.; Maan, A.; Abe, S.; van Duin, A. C.; Koel, B.E. (Frontiers in Physics, 2023)
Sputtering, reflection, and retention processes at amorphous and crystalline lithium hydride surfaces due to impact of low energy (1 - 100 eV) hydrogen and deuterium atoms over the range of 0o - 85o angle of incidence at 300 K surface temperature are investigated by atomistic computational methods. Classical molecular dynamics simulations are performed with improved reactive bond-order force field (ReaxFF) potentials, which include long-range polarization effects. In addition to probabilities of surface processes, the energy and angular spectra of ejected particles were obtained. Comparison of these results with those previously obtained on pristine lithium surfaces indicates importance of saturation of the Li surface and near-surface region with hydrogen. We show that such saturation, which is typical in both laboratory and fusion device experiments with lithium coating of the plasma-facing surfaces, significantly changes the surface processes with hydrogen irradiation in the understudied low-energy region of impact energies.